Inhibition of DNA and Histone Methylation by 5-Aza-2′-Deoxycytidine (Decitabine) and 3-Deazaneplanocin-A on Antineoplastic Action and Gene Expression in Myeloid Leukemic Cells - Momparler, Richard L.; Côté, Sylvie; Momparler, Louise F.; Idaghdour, Youssef (Frontiers in Oncology, 2017)
Epigenetic alterations play an important role in the development of acute myeloid leukemia (AML) by silencing of genes that suppress leukemogenesis and differentiation. One of the key epigenetic changes in AML is gene silencing by DNA methylation. The importance of this alteration is illustrated by the induction of remissions in AML by 5-aza-2'-deoxycytidine (5-AZA-CdR, decitabine), a potent inhibitor of DNA methylation. However, most patients induced into remission by 5-AZA-CdR will relapse, suggesting that a second agent should be sought to increase the efficacy of this epigenetic therapy. An interesting candidate for this purpose is 3-deazaneplanocin A (DZNep). This analogue inhibits EZH2, a histone methyltransferase that trimethylates lysine 27 histone H3 (H3K27me3), a marker for gene silencing. This second epigenetic silencing mechanism also plays an important role in leukemogenesis as shown in preclinical studies where DZNep exhibits potent inhibition of colony formation by AML cells. We reported previously that 5-AZA-CdR in combination with DZNep exhibits a synergistic antineoplastic action against human HL-60 AML cells and the synergistic activation of several tumor suppressor genes. In this report, we showed that this combination also induced a synergistic activation of apoptosis in HL-60 cells. The synergistic antineoplastic action of 5-AZA-CdR plus DZNep was also observed on a second human myeloid leukemia cell line, AML-3. In addition, 5-AZA-CdR in combination with the specific inhibitors of EZH2, GSK-126 or GSK-343, also exhibited a synergistic antineoplastic action on both HL-60 and AML-3. The combined action of 5-AZA-CdR and DZNep on global gene expression in HL-60 cells was investigated in greater depth using RNA sequencing analysis. We observed that this combination of epigenetic agents exhibited a synergistic activation of hundreds of genes. The synergistic activation of so many genes that suppress malignancy by 5-AZA-CdR plus DZNep suggests that epigenetic gene silencing by DNA and histone methylation plays a major role in leukemogenesis. Targeting DNA and histone methylation is a promising approach that merits clinical investigation for the treatment of AML.